ChemInform Abstract: Efficient Room‐Temperature Cooling with Magnets. Issue 40 (September 2016) - Boeije, M. F. J.; Roy, P.; Guillou, F.; Yibole, H.; Miao, X. F.; Caron, L.; Banerjee, D.; van Dijk, N. H.; de Groot, R. A.; Brueck, E.
Abstract: Polycrystalline MnFe0.95 P0.582 Si0.34 B0.078 with an Fe/Mn ratio of ≈1 is used to provide experimental evidence for the origin of the giant entropy change found for materials exhibiting a magnetocaloric effect in the form of an electronic reconstruction caused by the competition between magnetism and bonding.